Continuing professional development (CPD) in radiography: A collaborative European meta-ethnography literature review. Issue 1 (September 2017) - Wareing, A.; Buissink, C.; Harper, D.; Gellert Olesen, M.; Soto, M.; Braico, S.; Van Laer, P.; Gremion, I.; Rainford, L.
Abstract: Objectives: The aim of the study was to complete a collaborative review of Radiography continuing professional development (CPD) research material to support the production of European Federation of Radiographer Societies (EFRS) CPD recommendations. A meta-ethnography approach to literature review was applied focussing upon commonalities rather than discrepancies between research outcomes. This facilitated exploration of context across the geographical region of Europe with national variations in CPD governance. The seven phases of the meta-ethnographic approach were followed by two independent experienced researchers. A third researcher mediated the findings which were then explored collaboratively with the EFRS CPD working group for concordance. Key Findings: Phase seven of the meta-ethnography involved interpreting an expression of the synthesis from the previous stages. Six main corroborating themes emerged in this process and following mediation were expressed as themes; knowledge, skills & competency, needs/gap analysis, multi-layered/multi-modal, barriers and drivers; regulation vs autonomy; fostering collaboration – harnessing technology. Conclusion: The primary feature of CPD activity should be the resulting impact – to patients, the service, the profession and the individual; with all stakeholders working in partnership. CPD activity must be flexible/multi-modal to support the changing growth/dynamic workforce. All stakeholders should utilise communication and technology resources and make efforts to improve collaboration between the management, regulators and educators to support Radiographers to develop meaningful CPD. Health services across Europe are under increasing stress and a principal factor going forwards will be managing increasing demands on healthcare staff whilst supporting enhancement of the knowledge, skills and competency base. Highlights: CPD should have impact to patients, the service, the profession and the individual. CPD must be flexible/multi-modal to support the changing workforce. Collaboration between the stakeholders involved with CPD could be improved. The perceived 'importance' of barriers and drivers to CPD activity is changeable. Meta-ethnography methodology is useful for novice researchers.